2010
DOI: 10.1093/glycob/cwq090
|View full text |Cite
|
Sign up to set email alerts
|

Levels of specific glycans significantly distinguish lymph node-positive from lymph node-negative breast cancer patients

Abstract: One of the most urgent requirements in breast cancer is the development of a blood-based test for early detection and prognosis. Previously published results found a significant difference between specific glycan levels in patients with advanced breast cancer and healthy controls. The aim of this investigation was to address a more clinically relevant problem, i.e., whether the measurement of specific glycans could identify women with aggressive disease at an early stage. In order to reduce potential bias in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…In this study, we demonstrated the importance of the total glycomics of HD transgenic (R6/2) and WT mice (BCF1) using the glycoblotting method [35][36][37][38][39][40][41]47,56]. This technique enabled us to efficiently estimate the structure and quantify the total glycomes derived from the brain and serum glycoproteins and glycosphingolipids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated the importance of the total glycomics of HD transgenic (R6/2) and WT mice (BCF1) using the glycoblotting method [35][36][37][38][39][40][41]47,56]. This technique enabled us to efficiently estimate the structure and quantify the total glycomes derived from the brain and serum glycoproteins and glycosphingolipids.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, glycosylation changes in non-invasive bodily fluids, inter alia, serum, urine, plasma glycomes and on individual glycoproteins have been identified as promising biomarkers for the detection of prostate cancer [28], hepatocarcinoma cancer (HCC) and cirrhosis of the liver [35,36], pancreatic cancer [37], ulcerative colitis [38], and bladder cancer [39]. Measuring the degree of alteration of specific glycans in serum/plasma or whole blood has helped to provide a novel, noninvasive method for determining prognosis in cases of cancer and the existence of specific altered glyco-phenotypes, which might represent risk factors for the sequela of certain diseases [40][41][42][43][44]. Huntingtin protein targeting experiments have also been performed to understand the pathogenesis of HD [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations demonstrated that an individual glycan, A3F1G1, may be useful in the diagnosis of breast cancer, as the levels of A3F1G1 correlated better with the progression of the disease and occurrence of metastasis than the levels of CA15-3 [1]. Recent investigations have elucidated other potential glycan markers for use in prognosis determination in breast cancer [14,15]. Glycan analysis of serum from earlystage breast cancer patients who were lymph-node-positive and lymph-node-negative elucidated the existence of glycan differences between the two groups [14].…”
Section: Breast Cancermentioning
confidence: 99%
“…Recent investigations have elucidated other potential glycan markers for use in prognosis determination in breast cancer [14,15]. Glycan analysis of serum from earlystage breast cancer patients who were lymph-node-positive and lymph-node-negative elucidated the existence of glycan differences between the two groups [14]. Further analyses showed that the altered glycans (A3F1G1, A2F1G1 and FA2) could be used to distinguish the lymph-node-positive patients from the lymph-node-negative patients and as such may hold potential as a non-invasive method of prognosis prediction in breast cancer patients [14].…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation